Precious Data from Tiny Samples: Revealing the Correlation Between Energy Content and the Chemical Oxygen Demand of Municipal Wastewater by Micro-Bomb Combustion Calorimetry - Korth, Benjamin; Heber, Claudia; Normant-Saremba, Monika; Maskow, Thomas; Harnisch, Falk (Frontiers in Energy Research, 2021)
Wastewater treatment plants (WWTP) are aimed to be transformed from sinks into sources of energy and material. For fostering corresponding engineering efforts and economic assessments, comprehensive knowledge of the energy content of wastewater is required. We show in this proof-of-concept study that these data can be gathered by combining micro-bomb combustion calorimetry with freeze-drying. Thereby, the methodology for measuring the combustion enthalpy (ΔcH) of wastewater is significantly improved by decreasing the time demand for the drying process as only tiny amounts of samples are required. Here, the effluent of the primary clarifier of a wastewater treatment plant treating low-strength municipal wastewater was sampled on a weekly basis for 1 year, yielding 53 composite samples that were analyzed for ΔcH and standard wastewater parameters. A robust correlation between the chemical oxygen demand (COD) and ΔcH of −14.9 ± 3.5 kJ gCOD−1 (r = 0.51) was determined, verifying previous results obtained with more laborious and time-demanding methodologies. The global chemical energy potential of the sampled WWTP is presumably higher as the first treatment steps and losses during sample preparation reduced the amount of energy-rich compounds. A stronger correlation was observed between ΔcH and the biochemical oxygen demand (BOD5, r = 0.64), suggesting its usage for predicting the potential of wastewater as feedstock for biotechnological applications. This demonstrates that micro-bomb combustion calorimetry can be applied for deriving precious information on the energy content of wastewater from simple COD measurements.